Relationship of Low Maternal Vitamin D3 Level and Adverse Early Neonatal Outcomes - Kawakib Hussein Noamam1 , Thikra Najim Abdulla2 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Low serum vitamin D [25 (OH) D] levels have been shown to have multiple health-relatedimplications in females at childbearing age, during pregnancy, as well as in their children. Aim of thestudy: To assess the inverse relationship between vitamin D3 level and adverse neonatal outcomes usingparameters such as fetal birth weight, head circumference, Apgar scores, fetal respiratory distress syndrome,and rate of neonatal admission.Materials and methods: A prospective study was conducted on 100 early- and full-term pregnant women atAl-Elwiya Maternity Teaching Hospital in Baghdad from 1st of April 2017 to 31st of March 2018. Maternalvitamin D deficiency was confirmed based on levels <20 ng/mL.Results: The vitamin D3 levels in the studied pregnant women were categorized as follows: normal (45%),insufficiency (31%) and deficiency (24%). The significant adverse neonatal outcomes associated withvitamin D3 deficiency were low Apgar score (54.2%), low birth weight (91.7%), small head circumference(91.7%), respiratory distress syndrome (66.7%), and neonatal intensive care unit admission (66.7%).Conclusions: vitamin D3 deficiency among pregnant women is associated with prominent adverse neonataloutcomes.